Integrated Microbiome–Metabolome Analysis Reveals Stage-Dependent Alterations in Bacterial Degradation of Aromatics in Leptinotarsa decemlineata - Kang, Wei-Nan; Jin, Lin; Ma, Hong-Yu; Li, Guo-Qing (Frontiers in Physiology, 2021)
In order to avoid potential harms during pupation, the Colorado potato beetle Leptinotarsa decemlineata lives in two different habitats throughout its developmental excursion, with the larva and adult settling on potato plants and the pupa in soil. Potato plants and agricultural soil contain a specific subset of aromatics. In the present paper, we intended to determine whether the stage-specific bacterial flora plays a role in the catabolism of aromatics in L. decemlineata. KEGG pathway analysis of the operational taxonomic units obtained by sequencing of culture-independent 16S rRNA region enriched a group of bacterial genes involved in the elimination of mono- and polycyclic aromatics at the pupal stage, compared with those at the larval and adult periods. Consistently, metabolome analysis revealed that dozens of monoaromatics such as styrene, benzoates and phenols, polycyclic aromatics for instance naphthalene and steroids, were more abundant in the pupal sample. Moreover, a total of 7 active pathways were uncovered in the pupal specimen. These ways were associated with the biodegradation of benzoate, 4-methoxybenzoate, fluorobenzoates, styrene, vanillin, benzamide and naphthalene. In addition, the metabolomic profiles and the catabolism abilities were significantly different in the pupae where their bacteria were removed by a mixture of three antibiotics. Therefore, our data suggested the stage-dependent alterations in bacterial breakdown of aromatics in L. decemlineata.